Extending NoHR for OWL 2 QL - Costa, Nuno (2018)
Partially supported by Fundação para a Ciência e a Tecnologia under project PTDC/EIA-CCO/121823/2010 and strategic project PEst/UID/CEC/04516/2013. M. Knorr was also supported by grant SFRH/BPD/86970/2012.